Serum IL-6 AS A marker of immuno-inflammatory response to Zn-Mg alloy implants in porcine (Sus scrofa) - Hafizsha, Nabila Latifa; Safitri, Jessica Anggun; Ulfa, Rasyida; Khalid, Idham; Agung, Nabilah Putroe; Makmur, Ali; Fitriana, Rizky (The Faculty of Veterinary Medicine of Syiah Kuala University, 2025)
Background and Aim: The present study aimed to evaluate the immune-inflammatory response induced by ZnMg(3x) and ZnMg(4x) alloy implants in the porcine urinary bladder by measuring serum interleukin-6 (IL-6) levels.Materials and Methods: Nine porcines, aged 2-3 months old with 25-30 kg body weight, were divided into three groups: ZnMg(3x), ZnMg(4x), and control, while the observation time was performed on days 0, 14, and 28. Implantation was performed on the urinary bladder using cystotomy techniques. Measurement of IL-6 levels is done using enzyme-linked immunosorbent assay (ELISA). Data were analyzed statistically using analysis of variance (ANOVA).Results : The results showed that at day 0 for the ZnMg(3x) and ZnMg(4x) implants were 0.53 0.92 pg/mL and 0.10 0.17 pg/mL, respectively. On day 14, IL-6 levels in both implants decreased, although not significantly. On day 28, a slight increase was observed in ZnMg(3x) compared to ZnMg(4x), but this was also not significant (P0.05).Conclusion: Based on the results, Zn-Mg materials are suitable to be used as urinary stent base materials.